Cloning of genes that encode a new heat-labile enterotoxin of Escherichia coli. - Pickett, C L (1986)
The genes for a new enterotoxin were cloned from Escherichia coli SA53. The new toxin was heat labile and activated adenylate cyclase but was not neutralized by antisera against cholera toxin or E. coli heat-labile enterotoxin. Subcloning and minicell experiments indicated that the toxin is composed of two polypeptide subunits that are encoded by two genes. The two toxin subunits exhibited mobilities on polyacrylamide gels that are similar to those of cholera toxin and E. coli heat-labile enterotoxin subunits. A 0.8-kilobase DNA probe for the new enterotoxin failed to hybridize with the cloned structural genes for E. coli heat-labile enterotoxin.